War-time Nurseries, 1941 (pg. 1) (London, 1941)
1941 1939-1945 "War-time Nurseries, 1941 (pg. 1)" [HFR0056a], 1941, Trades Union Congress The June-July 1941 issue of the TUC's Industrial News Letter for Women focuses on the establishment of day nurseries for the children of war workers. From 1939, nursery centres were set up for evacuated young children. By May 1941, manpower shortages made the employment of married women essential and the Ministry of Health devised a national wartime nursery policy. Within six months, 194 nurseries had been opened and nursery classes added to primary schools. By September 1944, there were 2400 nurseries or nursery classes with over 106,000 children receiving organised care outside the home.